The Development of Mobile Base Interactive Learning Multimedia For Critical Thinking Improvement - Emma Valensia Aurum; Herman Dwi Surjono (Universitas Negeri Makassar, 2021)
This research study aimed to solve common problems often faced by learners. This is a Research and Development (R&D) with the APPED model which consistsconsisting of five stages of development. The subjects of this research were the 10th-grade students of the Vocational Program of Computer and Network Technology at SMK Negeri 1 Tulung Klaten (State Vocational School 1 of Tulung, Klaten). The data analysis were analyzed usingtechnique was done through the descriptive quantitative technique. Based on the research, the data from the validation of performed by experts and practitioners of mobile-based interactive learning multimedia, out of four validators, obtained showed an overall value of 87.92%, which was included incategorized in the very good category, and meaning that it is proper for use in learning. The N-gain of Tthe critical thinking ability improvement at the application stage obtained an N-gain ofwas 82.9%, and it waswhich was categorized as included in the medium improvement category. The effectiveness of interactive learning multimedia used in learning as, shown by the learners’ response questionnaires, obtained showed an overall percentage of 83.52% and was included in the very good category. Based on the Wilcoxon test on critical thinking ability data, and the pretest-posttest gain values, critical thinking ability it obtained a value of 0.000 which indicated that there was a difference in the critical thinking ability improvement in after using the mobile-based interactive learning multimedia. Therefore, mobile-based interactive learning multimedia can be used as an alternative medium in learning to help improve students' critical thinking ability, as well as to support the independent learning process.